The influence of NIM, BOPO, LDR, and size toward Return On Assets (ROA) and its relations with technical efficiency on banks (Buku 4) in Indonesia - Gusnaleven Parhusip; Pandu Adi Cakranegara (IDEAS: Journal of Management & Technology, 2021)
This study aims to know the influence of NIM, BOPO, LDR, and Size toward Return on Assets (ROA) and its relations with technical efficiency. Data Envelopment Analysis (DEA) approach is used to measure technical efficiency. This study also uses multiple regression analysis methods. It takes banks BUKU 4 in Indonesia from the first quarter of 2018 to the fourth quarter of 2020 as the sample. The finding also reveals that there is a weak correlation between technical efficiency and ROA. Meanwhile, NIM and Size have a significant positive impact on ROA. BOPO has a significant negative impact on ROA. Meanwhile, LDR has an insignificant positive impact on ROA. Simultaneously, those independent variables have a significant effect on ROA. Among the independent variables, NIM is the most significant towards ROA.